2021
DOI: 10.1002/ps.6676
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics of imidacloprid in cotton flower, nectariferous tissue, pollen and Apis mellifera products using QuEChERS method

Abstract: BACKGROUND: Exposure of Apis mellifera to neonicotinoid insecticides is one of the factors attributed to the recent decline in A. mellifera populations resulting in economic and ecological losses due to loss of pollination services. Honey bees can get exposed to neonicotinoids like imidacloprid directly in the field at the time of application as well as during consumption of pollen and nectar from treated plants. So, the fate of imidacloprid in commodities to which honey bees get exposed needs to be overhauled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(48 reference statements)
2
5
0
Order By: Relevance
“…IMI was a systemic pesticide, which was easily absorbed by plants. Kaur Brar et al reported that IMI residue was 1.95 mg/kg in cotton flowers and 0.24 mg/kg in nectariferous tissue after IMI was sprayed . The concentration ranges were close to those in this experiment.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…IMI was a systemic pesticide, which was easily absorbed by plants. Kaur Brar et al reported that IMI residue was 1.95 mg/kg in cotton flowers and 0.24 mg/kg in nectariferous tissue after IMI was sprayed . The concentration ranges were close to those in this experiment.…”
Section: Resultssupporting
confidence: 85%
“…Kaur Brar et al reported that IMI residue was 1.95 mg/kg in cotton flowers and 0.24 mg/kg in nectariferous tissue after IMI was sprayed. 31 The concentration ranges were close to those in this experiment. The half-life of IMI was about 3−7 days in crop, for example, capsicum, and the degradation rate was relatively high.…”
Section: Effect Of Coexposure Of Otc On the Residue Of Imi In Radishsupporting
confidence: 85%
“…For example, the contents of imidacloprid sprayed were different in cotton flowers, leaves, nectary tissues and pollens, being highest in leaves, but not detected in the nectary tissues and pollens after seed treatment. 4,25 Thiamethoxam could be absorbed by roots and transported upwards rapidly to control sucking mouthparts pests, but difenoconazole without root absorption was used only to control rice diseases by stem and leaf spray. [26][27][28] Surprisingly, this study showed that matrine could be rapidly absorbed by the roots, leaves and seeds of both pepper and wheat, and transmitted into all organs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different systemic pesticides have different transmission directions in plants – upwards, downwards or bidirectionally – and their conduction modes, velocities and biological concentrations are different when treating different plant organs. For example, the contents of imidacloprid sprayed were different in cotton flowers, leaves, nectary tissues and pollens, being highest in leaves, but not detected in the nectary tissues and pollens after seed treatment 4,25 . Thiamethoxam could be absorbed by roots and transported upwards rapidly to control sucking mouthparts pests, but difenoconazole without root absorption was used only to control rice diseases by stem and leaf spray 26–28 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, there have been concerns about the pesticide in context to the occupational hazards, residues in food and water above the permissible limit even though these are manufactured under strict regulation to function with certainty and minimal effect on non-target organisms (Damalas and Eleftherohorinos, 2011). There are reports of exposure of non-targent organisms like pollinators to pesticides resulting in economic and ecological losses (Brar et al, 2022). So, it becomes important to have vast knowledge about the nature of pesticide to be applied, their movement in soil and various tactics to prevent their risk to non-target organisms.…”
mentioning
confidence: 99%